Fast Hybrid Method for the Study on Monostatic Scattering from Plasma-Coated Target above a Rough Surface - Rui Wang; Shui-Rong Chai; Li-Xin Guo (International Journal of Antennas and Propagation)
A fast hybrid method combining the reciprocity theorem with high frequency approximation algorithm is presented to deal with the problem of the monostatic scattering from a two-dimensional (2D) plasma-coated target above a one-dimensional (1D) Gaussian rough surface illuminated by the tapered incident wave. Without numerical solution of the polarization currents on the target and the surface, this hybrid method does not only save computer resources but also improve the computing speed significantly in contrast to the numerical methods. The hybrid method based on equivalent principle and reciprocity theorem, which is an improved and generalized version of the traditional multipath technique, can deal with the interactions between plasma-coated target and underlying surface much more accurately. Numerical results are given to verify the validity of the hybrid method, and then the hybrid method is employed to investigate the monostatic scattering from a plasma-coated airfoil above a Gaussian rough surface, including the effects of several key parameters on stealth performance, such as plasma angular frequency and electron collision frequency.